SPA DENGAN PENDEKATAN ARSITEKTUR TROPIS DI KABUPATEN BENGKAYANG - Ayunita, Rida Rizkika (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2022)
Technological advances in internet use have affected new lifestyles for urban communities. In the time of the Covid-19 virus pandemic, the use of internet technology became more intense because of work, education, and other things implementing the Work From Home (WFH) system. This can trigger stress due to work time and not working that has melted as if it does not know the time. Concerns about the health of urban communities due to high levels of stress give rise to the phenomenon of therapeutic tourism as a means for relaxation and recreation in one area. The design ofÂ â€œSPA Dengan Pendekatan Arsitektur Tropis di Kabupaten Bengkayangâ€ with destination SPA program is seen as an opportunity aimed at preventing, healing, and restoring one's physical and psychic state. Destination SPA has facilities in the form of complete SPA services, body treatments, hot spring baths, health education, healthy cuisine, beauty treatments, fitness, as well as rental and room service. Samudera Indah Beach is one of the beach attractions in Bengkayang Regency, is a tourism development area with beautiful scenery. Tropical Architecture approach in SPAtial and building arrangement is applied in order to solve tropical climate problems at the design site and can realize natural impressions in accordance with the nature of nature. The methods used in this design, namely the idea stage, the data collection stage, the analysis stage, the synthesis stage, the pre-draft stage, and the planning stage.